2014
DOI: 10.3390/f5092327
|View full text |Cite
|
Sign up to set email alerts
|

A Scenario-Based Method for Assessing the Impact of Suggested Woodland Key Habitats on Forest Harvesting Costs

Abstract: Variable retention harvesting is acknowledged as a cost-effective conservation measure, but previous studies have focused on the environmental value and planning cost. In this study, a model is presented for optimizing harvesting cost using a high resolution map generated from airborne laser scanning data. The harvesting cost optimization model is used to calculate the objective value of different scenarios. By comparing the objective values, better estimates of the opportunity cost of woodland key habitats ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…An example of the former is (Granhus et al, 2011), who used cost functions adapted from Dale and Stamm (1994)) to calculate the harvesting cost. Examples of the latter include (Contreras and Chung, 2007), who modified a regression model by (Han and Renzie, 2005), and (Søvde et al, 2014) who modified results found by (Nurminen et al, 2006). On the other hand, large scale follow-up studies based on production reports provide robust but more generalised productivity functions (Eriksson and Lindroos, 2014;Purfürst, 2010).…”
Section: Line G)mentioning
confidence: 99%
See 1 more Smart Citation
“…An example of the former is (Granhus et al, 2011), who used cost functions adapted from Dale and Stamm (1994)) to calculate the harvesting cost. Examples of the latter include (Contreras and Chung, 2007), who modified a regression model by (Han and Renzie, 2005), and (Søvde et al, 2014) who modified results found by (Nurminen et al, 2006). On the other hand, large scale follow-up studies based on production reports provide robust but more generalised productivity functions (Eriksson and Lindroos, 2014;Purfürst, 2010).…”
Section: Line G)mentioning
confidence: 99%
“…This model is sometimes referred to as the network method (Søvde, 2014), and has found some applications in the literature (e.g. Contreras and Chung, 2007;Chung et al, 2008;Contreras and Chung, 2011;Søvde et al, 2014). The network model is usually formulated as a shortest path problem (SPP), using a digital terrain model (DTM) as input (Line B or Line C in Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…For example, the costs of legislation and management necessary to maintain forest ecosystem services could be offset by environmental taxes, and these costs can be estimated. Existing studies have simulated the opportunity cost to manage the old-growth forest and endangered species instead of timber production-focused forest management [5], while other studies have calculated forest operation cost and the opportunity cost of forest habitats with a model for optimizing harvesting costs using a high-resolution map generated from airborne laser scanning data [6].…”
Section: Introductionmentioning
confidence: 99%